Online continuing medical education as a key link for successful noncommunicable disease self-management: the CASALUD™ Model - Gallardo-Rincón H (Dove Medical Press, 2017)
Héctor Gallardo-Rincón,1 Rodrigo Saucedo-Martínez,1 Ricardo Mujica-Rosales,1 Evan M Lee,2 Amy Israel,2 Braulio Torres-Beltran,3 Úrsula Quijano-González,3 Elena Rose Atkinson,3 Pablo Kuri-Morales,4 Roberto Tapia-Conyer1 1Fundación Carlos Slim, Mexico City, Mexico; 2Lilly Global Health, Eli Lilly and Company, Vernier, Switzerland; 3C230 Consultores, Mexico City, Mexico; 4Mexican Ministry of Health, Mexico City, Mexico Purpose: The purpose of this study is to evaluate how the benefits of online continuing medical education (CME) provided to health care professionals traveled along a patient “educational chain”. In this study, the educational chain begins with the influence that CME can have on the quality of health care, with subsequent influence on patient knowledge, disease self-management, and disease biomarkers. Methods: A total of 422 patients with at least one noncommunicable disease (NCD) treated in eight different Mexican public health clinics were followed over 3 years. All clinics were participants in the CASALUD Model, an NCD care model for primary care, where all clinic staff were offered CME. Data were collected through a questionnaire on health care, patient disease knowledge, and self-management behaviors; blood samples and anthropometric measurements were collected to measure patient disease biomarkers. Results: Between 2013 and 2015, the indexes measuring quality of health care, patient health knowledge, and diabetes self-management activities rose moderately but significantly (from 0.54 to 0.64, 0.80 to 0.84, and 0.62 to 0.67, respectively). Performing self-care activities – including owning and using a glucometer and belonging to a disease support group – saw the highest increase (from 0.65 to 0.75). A1C levels increased between 2013 and 2015 from 7.95 to 8.41% (63–68 mmol/mol) (P<0.001), and blood pressure decreased between 2014 and 2015 from 143.7/76.8 to 137.5/74.4 (systolic/diastolic reported in mmHg) (P<0.001). The mean levels of other disease biomarkers remained statistically unchanged, despite the improvements seen in the previous “links” of the educational chain. Conclusion: Online CME can effect certain changes in the educational chain linking quality of health care, patient knowledge, and self-management behaviors. However, in order to assure adequate NCD control, the entire health care system must be improved in tandem. Online CME programs, such as CASALUD’s, are feasible strategies for impacting changes in disease self-management at a clinic level throughout a country. Keywords: chronic disease, health education, type 2 diabetes mellitus, Mexico, continuing medical education, primary care